Effect of chain extender on structural and mechanical properties of poly(butylene succinate‐co‐adipate)/halloysite nanotube bionanocomposites. (30th November 2020) - Prashantha, Kalappa; Rashmi, Baralu J.
Abstract: Bionanocomposites comprising poly(butylene succinate‐co‐adipate) (PBSA) and halloysite nanotubes (HNTs) were fabricated via melt extrusion using different HNT loadings. These nanocomposites were characterized through Fourier transfer infrared spectroscopy, X‐ray diffraction, scanning electron microscopy, and mechanical, thermal, and rheological tests. Adding a chain extender (CE) ensured homogeneous dispersion of HNTs in the PBSA matrix because the epoxy‐based CE and HNTs reacted with the carboxyl groups of PBSA, leading to effective interfacial interactions between the matrix and reinforcing filler. Differential scanning calorimetry results revealed that HNTs had a nucleating effect on PBSA, thereby increasing the crystallization of PBSA and percentage crystallinity of the composites. Nevertheless, the CE did not cause any change in the crystallinity of the nanocomposites. Further, the thermal stability of PBSA without and with the CE reduced, depending on the HNT loading. The HNTs and CE also increased the melt strength of PBSA. Additionally, HNTs and CE enhanced the mechanical properties owing to the increased molecular weight and formation of long‐chain branched structures.